Photochemically Prepared Gold/Polymer Nanocoatings: Formation of Gold Mirror - Ceper, Tolga; Arsu, Nergis (WILEY-V C H VERLAG GMBH, 2017)
In this study a rapid method is developed to obtain Au nanoparticles(AuNPs)/polymer composite materials by which HAuCl4 salt is reduced and a polymer matrix is simultaneously generated by the means of UV light. 2-Mercaptothioxanthone (TX-SH), thioxanthone (TX), and TX + thiophenol are used as photoinitiator system for the poly(ethylene glycol) methyl ether acrylate and poly(ethylene glycol) diacrylate mixtures in the presence of HAuCl4. Except for a few studies, in situ reduction of Au ions, in an attempt to make them near or at polymer surface, has hardly been investigated at all. As a result of this study, it is important to note that the change of shape of NPs depends on the photoreducing species. TX-SH, due to thiol functionality in its structure, helps the production of the size, shape, and controlled distribution of AuNPs either in polymer matrix or in solution. Prepared AuNPs/polymer nanocoatings exhibit a reflected gold mirror view depending on the irradiation time. In addition to the foregoing approach in obtaining a thin film in the presence of AuNPs, it is expected that they are well ordered near the film surface with controlled shape and narrow range in size distribution.
Keywords: functional coatings; gold nanoparticles; nanocomposite films; nanogold mirror; photochemical preparation; SILVER-EPOXY NANOCOMPOSITES; FREE-RADICAL POLYMERIZATION; II PHOTOINITIATOR; ELECTRON-TRANSFER; NANOPARTICLES; LIGHT; FABRICATION; ROUTE; NOBLE; FILMS; Polymer Science